If You Don't Feed the Students, They S.T.A.R.V.E. : Improving Attitude and Achievement Through Positive Relationships - Connors, Neila A. author 374976 (San Francisco, CA : Jossey-Bass, 2020)
"The author uses the metaphor of dining as a framework to provide educators and others who work with pre-K- 12th grade students strategies, techniques, and realistic ideas to develop, maintain, and sustain positive relationships. If you don't F.E.E.D. (Fuel Education Every Day) the students, they S.T.A.R.V.E. (Stop Trying And Reject Valuable Education). The focus is on the recognition of all students (schools where everybody is somebody) and creating a climate of care and compassion"--